Walking in indeterminate spaces: possibilities for political co-existence. (14th November 2016) - Phillips, Louise Gwenneth
Abstract : Purpose: The purpose of this paper is to discuss how being led by a young child to unknown destinations without shared language offers an experience of indeterminacy that opens up (re)thinking of political co-existence. Design/methodology/approach: The relational arts project The Walking Neighbourhood hosted by children challenges the social practice of adults chaperoning children through public streets by inviting children to curate and lead unknown adults on walks of local neighbourhoods. This paper focusses on sensory ethnographic research of one encounter of a child-curated walk when this project took place in Chiang Mai, Thailand. The experience is relayed through multilayered sensorial storytelling inter-woven with diffractive analysis informed from a post-humanist agential realist position (Barad, 2007, 2012). Findings: Perceptions, knowings, imaginings, memories and connections are read as explanations of intra-actions in the child-led walk to produce new meaning in the phenomena of political co-existence. Emergent, embodied, sensorial listening produces new awareness and understandings of intra-acting beings in an urban space regardless of age or form. Social implications: Application of ethical ontological epistemological practice through emergent, embodied, sensorial listening to others opens affectual ethical ways of being and knowing for justice-to-come in political co-existence. Originality/value: The concept of child-led walks is innovative as a political act by shifting from vertical adult-child relations to horizontal relations. Post-humanist agential realism is a new and emerging theory that offers possibilities to reconceptualise co-existence with others in public spaces.